(untitled) (Sustainability in Debate, 2014)
The work presented here was developed in a PhD research. We chose two performative actions carried out in the context of prevention projects of gender violence in Porto between 2009 and 2010, articulated with formal educational processes, non-formal and informal. The actions under review are as follows: 1: Cry for Justice; 2: Traffic of human beings Visual analysis within the framework of cultural anthropology was our methodological choice, putting up an improvisational approach to the film, a mix of film essays taken from the immediate social and cultural context and involved in a detached situation of their daily lives. Also we seek to consistently articulate the link between art as a means of social transformation and the debate on sustainability. We consider that the objective has been achieved, since the audience participated by showing interest and actions we felt, still, he was impressed by these problems.